Analysis of Water Quality in Historical Shipwreck Sites to Support the Development of Marine Ecotourism in the Thousand Islands - Rustam Agustin (EDP Sciences, 2021)
Thousand Islands has become the main focus of the marine tourism development in Special Capitol Region of Jakarta (DKI Jakarta). In this regard, one of the marine tourism objects proposed to be further developed is historical shipwreck diving as a new marine ecotourism attraction in the Thousand Islands. The historical sites of shipwrecks that are widely scattered underwater are expected to give added value to the beauty of underwater panorama because most of the sites have been covered with coral reefs adding to the uniqueness to the underwater diving attractions. However, the high activity on the North Coast of Java area and surrounding islands tends to affect the water quality and the presence of shipwrecks assuming it will be used for the development of diving tourism. This study aims to determine the carrying capacity of water quality on shipwrecks based on in situ water quality measurement and image analysis. The method of data collection and analysis carried out is a combination of in situ measurements at the location; analysis of water samples with laboratory testing and analysis of Landsat 8 satellite imagery. The result showed that nutrient and orthophosphate values of nitrate, which supported the life of marine biota and micro-algae that helped the biota’s biofouling process, increased the site’s attractiveness from 0.094 – 0.101 mg/L and 0.005 – 0.008 mg/L, respectively. Furthermore, other water quality values measured are still in accordance with quality standards for marine life survival on shipwrecks and ecotourism, especially dive spots with clear water visibility.